2016
DOI: 10.4236/ajcc.2016.51012
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in Precipitation Projection under Changing Climate Conditions: A Regional Case Study

Abstract: This study investigates different sources of uncertainty in the assessment of the climate change impacts on total monthly precipitation in the Campbell River basin, British Columbia, Canada. Four global climate models (GCMs), three greenhouse gas emission scenarios (RCPs) and six downscaling methods (DSMs) are used in the assessment. These sources of uncertainty are analyzed separately for two future time periods (2036 to 2065 and 2066 to 2095). An uncertainty metric is calculated based on the variation in sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Hence, it is important to use multiple DSMs during climate change impact assessment. Mandal et al () reached a similar conclusion in the study of Pr projection under changing climatic conditions. It is to be expected that if the Pr pattern is affected, then the streamflow will change too.…”
Section: Conclusion and Summarysupporting
confidence: 54%
See 1 more Smart Citation
“…Hence, it is important to use multiple DSMs during climate change impact assessment. Mandal et al () reached a similar conclusion in the study of Pr projection under changing climatic conditions. It is to be expected that if the Pr pattern is affected, then the streamflow will change too.…”
Section: Conclusion and Summarysupporting
confidence: 54%
“…According to Prudhomme and Davies (), selection of AOGCMs creates more uncertainty in the downscaling process compared to the choice of emission scenarios or model parameterization. However, its also found that downscaling methods might be a significant source of uncertainty in hydrologic projections compared to the choice of climate models and emission scenarios that are a much less significant source of uncertainty (Bürger, Sobie, Cannon, Werner, & Murdock, ; Mandal, Breach, & Simonovic, ). All the studies mentioned above they investigated only changes in climatic variables, for example, temperature or precipitation (Pr).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of future concentration scenarios, this study made use of the precipitation simulations for all four RCP scenarios (RCP2.6, RCP4.5, RCP6.0, RCP8.5). However, all RCPs have not been mostly considered in hydrological impact studies of climate change (Booth et al, 2013;Mohammeda et al, 2015;Fatichi et al, 2016;Mandal et al, 2016;Monjo et al, 2016) and for simplifying and based on the research purpose, the climate model outputs for only one RCP (RCP8.5 representing the extreme future conditions or RCP4.5 representing the medium future conditions) or two RCPs (RCP4.5 & RCP8.5) have been used. From uncertainty analysis point of view, all RCPs are needed to cover the total ensemble uncertainty of climate change.…”
Section: Climate Change Signal Uncertainty For Idf Relationships and mentioning
confidence: 99%
“…The application of multi‐model ensembles to quantify the projection uncertainty of climate change has recently increased in hydrological studies (Minville et al ., ; Chen et al ., ; Hughes et al ., ; Kingston et al ., ; Dessu and Melesse, ; Mandal et al ., ). The larger the ensemble size of independent climate models considered, the better the quantification of climate change uncertainty would be.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation